Pengaruh Literasi Keuangan dan Financial Technology terhadap Pengelolaan Keuangan Studi UMKM Roti di Kecamatan Sukodono - Ramadani, Putri Amalia; M Mustaqim (Universitas Nahdlatul Ulama Sidoarjo, 2025)
This study aims to analyze the Influence of Financial Literacy and Financial Technology on Financial Management (Study of Bread MSMEs in Sukodono District). The method used is a quantitative approach with data collection through questionnaires distributed to 94 respondents. The results of the study indicate that Financial Literacy has a significant and positive influence on MSME Financial Management, which means that the better the financial knowledge of business actors, the more effective their Financial Management. Conversely, Financial Technology does not show a significant influence on Financial Management. Simultaneously, Financial Literacy and Financial Technology have a positive influence on MSME Financial Management. This finding emphasizes the importance of increasing Financial Literacy for MSME actors as an effort to support the sustainability of their business. The data analysis tool used to test the hypothesis is SPSS 25.0 software.